Analisis Kesenjangan Pembangunan Antara Wilayah Perkotaan dan Pedesaan: Studi Kasus Kota Serang dan Desa Cikedung, Kabupaten Serang - Arafat, Yasir; Rahadatul Aisyi Rafillah; Diva Aditiya Tahir; Dwi Wulan Dari; Audry Bunga Natasya; Ibnu Malikil Ulum (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study discusses the development gap between Serang City and Cikedung village in Serang Regency. Cikedung village is lagging behind in terms of infrastructure, education, health, and economic access, despite having great natural resource potential. The condition of damaged roads, limited public facilities, and the lack of attention of local governments are the main obstacles in village development. Meanwhile, Serang City shows rapid progress with a high Human Development Index (HDI), adequate public facilities, and economic structure that has shifted to the tertiary sector. This inequality is also seen in the Gross Regional Domestic Product (GRDP), where Serang city is dominated by the trade and service sectors, while Cikedung village still relies on a limited agricultural sector and is less driven by policy. In addition, structural barriers such as protected forest land status and bureaucratic procedures exacerbate village isolation. This study emphasizes the importance of equitable development and policies that are responsive to the periphery. Without a change in policy direction, villages like Cikedung will continue to lag behind and only become resource providers without enjoying fair and sustainable development results.